2012
DOI: 10.1007/s10802-012-9679-7
|View full text |Cite
|
Sign up to set email alerts
|

Etiological Contributions to the Covariation Between Children’s Perceptions of Inter-Parental Conflict and Child Behavioral Problems

Abstract: Prior work has suggested that inter-parental conflict likely plays an etiological role in child behavior problems. However, family-level measurement of inter-parental conflict in most traditional child twin studies has made it difficult to tease apart the specific causal mechanisms underlying this association. The Children’s Perception of Inter-parental Conflict scale (CPIC) provides a child-specific measurement tool for examining these questions, as its subscales tap multiple dimensions of conflict assessed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Lower levels of coping self‐efficacy for avoiding maladaptive cognitions and coping self‐efficacy for avoiding maladaptive behaviors were expected to be associated with higher levels of internalizing, externalizing, and anxiety. Given that Brummert Lennings and Bussey showed that the reliability and validity of the PCC‐SES was equally applicable across gender and grade, it was expected that, consistent with past studies, the relationship between the variables would remain the same regardless of gender and age (see Cummings et al, ; Nikolas, Klump, & Burt, ).…”
Section: Introductionmentioning
confidence: 75%
“…Lower levels of coping self‐efficacy for avoiding maladaptive cognitions and coping self‐efficacy for avoiding maladaptive behaviors were expected to be associated with higher levels of internalizing, externalizing, and anxiety. Given that Brummert Lennings and Bussey showed that the reliability and validity of the PCC‐SES was equally applicable across gender and grade, it was expected that, consistent with past studies, the relationship between the variables would remain the same regardless of gender and age (see Cummings et al, ; Nikolas, Klump, & Burt, ).…”
Section: Introductionmentioning
confidence: 75%
“…For the current study, we focused specifically on the Conflict Properties scale (n=11 items, α = .77), which assesses the frequency and intensity of inter-parental conflict as observed by the child (e.g., “My parents get really mad when they argue”). The other three scales on the CPIC (namely, Threat, Self-Blame, and Triangulation/Stability) were not examined because they assess the child’s emotional and/or cognitive appraisals of inter-parental conflict (e.g., “I am to blame when my parents argue”) rather than their observations (Nikolas et al ., 2010, Nikolas et al ., 2013). …”
Section: Methodsmentioning
confidence: 99%
“…In doing so, we make use of several measurement strategies: parent- and child-informant reports, videotaped parent–child, family, and spousal interactions, and the assessment of an independent sample of neighborhood informants from each twin family’s neighborhood. The TBED-C has already produced several published papers (Burt & Klump, 2012, in press-a; Burt et al, 2012; Humbad et al, 2011; Klahr et al, in press; Marceau et al, 2012; Nikolas et al, 2012, in press), with many more under review and in preparation.…”
Section: Msutr Projectsmentioning
confidence: 99%
“…Observational as well as survey methods comprise our assessments of parent–child, familial, and spousal relationships. This multi-method approach allows us to more rigorously define our phenotype (Burt, 2012; Burt & Klump, 2012), examine informant effects on heritability estimates (Marceau et al, 2012; Nikolas et al, in press), and obtain a more fine-tuned understanding of environmental risks and their contributions to psychiatric outcomes (Burt et al, 2012; Burt & Klump, in press-a, 2012; Nikolas et al, 2012). …”
mentioning
confidence: 99%